The Influence of Asset Growth And Net Profit on The Financial Performance of Pt Jamkrindo Syariah For The Period 2019-2023 - Revan Andhitiyara; Dimas Subekhi; Sita Dewi; Hadi Santoso; Francisca Hermawan; Gemala Paramita (International Journal of Informatics, Economics, Management and Science, 2025)
Financial performance is one of the important aspects that reflects the condition and ability of a company in carrying out its operations to achieve predetermined goals. To achieve optimal financial performance, companies must be able to manage various factors that affect company value, including asset growth and net profit. Asset growth illustrates the company's ability to accumulate economic resources that can be used to increase operational capacity. Well-managed assets can improve operational efficiency and drive increased revenue. Net profit is derived from revenue, expense, profit, and loss transactions. Net profit reflects the final result of a company's overall operating activities after deducting expenses, including taxes. Net profit is an important indicator for investors and management in assessing how effective the company is in maximizing profits from its assets. The management of asset growth and net profit is important for the company's success in improving its financial performance. By taking the object of research PT. Jamkrindo Syariah, the purpose of this study is to determine the effect of asset growth and net profit on financial performance, both partially and simultaneously. The data is the monthly financial statements of PT Jamkrindo Syariah for the period 2019-2023 and data analysis using multiple linear regression and correlation analysis. The results showed that asset growth had no effect on financial performance, while net income had a significant positive effect on financial performance. Simultaneously asset growth and net income have a significant positive effect on financial performance.